What Creates Listening Online? Exploring Reciprocity in Online Political Discussions with Relational Content Analysis - Dennis Friess; Katharina Esau (Journal of Deliberative Democracy)
Democratic governments frequently use online tools to include large numbers of citizens in participation processes. Against the backdrop of deliberative theories, such initiatives are subject to normative needs. This article examines the equality of participation. Previous research has mainly focused on equality in terms of access to, and voice within, deliberation processes. However, much less is known about the factors that influence the distribution of reciprocity in online political discussions. Proposing a theoretical distinction between simple replying and deliberative reciprocity, this study addresses the question: What obstructs or promotes deliberative reciprocity online? Drawing on previous online communication research, we assume that communication style, gender and users’ activity are important predictors of simple replying and deliberative reciprocity. Results of a relational quantitative content analysis indicate that in order to receive deliberative reciprocity users should ask questions, propose arguments, be humorous, have a critical attitude and use a male user name. Storytelling and expressions of emotions show no significant associations with deliberative reciprocity.